How HIV causes disease 1: identification and characterization of HIV - Walker, Bruce (Henry Stewart Talks, 2019)
Original description of AIDS, Identification of HIV as a causative agent, Evidence that HIV causes AIDS, Molecular mechanisms of HIV infection